(untitled) (Journal of Misan Researches, 2022)
The research aims to know the most important obstacles facing e-learning at the University of Maysan from the point of view of the faculty members through a questionnaire prepared by the researcher to identify the obstacles that consisted of (23) paragraphs distributed on four axes: Aspects related to the teaching and the student (8) Obstacles The third axis: Aspects related to e-learning (5) Obstructed and the fourth axis: The educational level (4) Obstructed. The questionnaire was presented to the arbitrators. The validity and reliability of the questionnaire was tested, which achieved 89% and the research tool was applied to the study sample which included (60) teaching staff members at the University of Maysan. The researcher used statistical standards and measures that fit the subject of the research and the results were drawn. The study came out with several conclusions, in the light of which a number of recommendations were identified, the most important of which is to benefit from the results of the current study in technicians, the most important obstacles to control Obstacles to e-learning at the University of Maysan and the qualification of male and female teachers to use e-learning platforms and modern means to identify the most important strengths and weaknesses of Improving professional performance.